Elisabetta Caminer and Melchiorre Cesarotti between Voltaire and Helvétius: new contributions to Veneto’s Enlightenment - Selmi, Elisabetta (Itinerari, 2023)
This paper explores the intellectual context of the Eighteen-century Venetian Enlightenment, with a special focus on the contribution of Elisabetta Caminer Turra (1751-1796). She was a playwright, a philosopher, a translator, and she played a central role in the circulation of the ideas of French philosophes des lumières in Venice. Furthermore, she worked both as a journalist and as an editor in the Giornale enciclopedico, and in the Nuovo giornale enciclopedico, which she founded in 1783. Through an analysis of several of Caminer’s writings this paper shows that her thought was inspired by Melchiorre Cesarotti (1730-1808), especially his Saggio sulla filosofia del gusto (‘Essay on the Philosophy of Taste’, 1784), and it combined elements coming from Voltaire’s rejection of prejudice with aesthetic categories taken from Locke’s empiricism, Hume’s sensism and Helvetius’ physical sensibility.